Avaliação da eficiência da espécie vegetal ouratea parviflora como inibidor de corrosão em aço carbono - Neri, Renaly dos Santos (2018)
The impacts of corrosion are frequent and occur in various activities. There are several ways of combating impacts, among them the use of micro-emulsified system have been targeted as corrosion inhibitors. Although they are effective in the corrosion control, some have high cost and are toxic to the environment, making its use questionable. In order to fulfill the growing demand for corrosion inhibitors, the objective of the present work was to perform a research about the inhibitory action of almonds oil and hydro-alcoholic extract from vegetal specie Ouratea parviflora. The extract was evaluated in free formand in a microemulsified system, containing the oil of the almonds in your composition, with different concentrations, regarding the corrosion inhibition efficiency into a saline medium (NaCl 3.5%). Was used the method Linear Polarization Resistance method, also determining the behavior and the isotherm of the metal/inhibitor adsorption process. According to the obtained results, the maximum inhibition efficiencies were observed at 67.70% (12.5 ppm), 77.94% (200 ppm) and 85.66% (200 ppm) to the free hydro-alcoholic extract, saline microemulsified system (SME-S) and saline micro-emulsified system with extract (SME-S-EB), respectively. In addition, all the experimental data from the adsorption process fitted the Langmuir isotherm. According to the data calculated from Gibbs free energy, it was detected a spontaneity of the adsorbent inhibitors used in different conditions on the steel surface. The study of getting of inhibitors used in different conditions under the sustainability bias confirmed that these formulations can be considered as sustainable. The results showed that the hydro-alcoholic extract of Ouratea parviflora evaluated in free form and in a microemulsion system containing the oil of the almonds of the same plant species, can be used as alternative sources in the formulation of corrosion inhibitors.